UMPSA receives IMI Accreditation as a Hybrid and Electric Vehicle Training Centre - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 21 March 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is the only public university in Malaysia to receive the United Kingdom's Institute of the Motor Industry (IMI) International Certification as one of the hybrid and electric vehicle training centres.